Physicochemical and Organoleptic Properties of Crackers From Native and Heat Moisture Treatment (HMT) of Breadfruit Flour - Irfan Djailani; Al Matin Hakim; Fahrizal Fahrizal; Yuliani Aisyah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
Crackers are one of the biscuit are made through a fermentation process with yeast, thin in shape, salty taste, crunchy texture, and if broken the cross-section of the pieces is layered. The main ingredient of crackers is flour. The purpose of this study was to determine the effect of varying concentrations of native and HMT modification of breadfruit flour on the physicochemical and organoleptic composition of crackers and to obtain the selected concentrations. This research was conducted experimentally using a completely randomized design with six treatments and three replications. The treatment for this study were SK1 (50% native breadfruit flour), SK2 (75% native breadfruit flour), SK3 (75% native breadfruit flour), SK4 (50% modified breadfruit flour), SK5 (75% modified breadfruit flour), and SK6 (100% modified breadfruit flour). Flour physical test data were analyzed using the T-test, while the physical test data of crackers and organoleptic assessment were ANOVA and continued with duncan's multiple range test (DMRT) at the 5% level. The results showed that the percentage of native breadfruit flour and modified breadfruit flour had a significant effect on bake loss, crispness, and sensory assessment. The best treatment in this study was SK4 with bake loss value of 18.27 g, crispness of 2.13kgF, moisture content of 7.42%, ash 2.76%, protein 7.85%, fat 13.40%, carbohydrate 68.57%, and fiber 3.05%. Hedonic sensory assessment with color score 4.06 (like), aroma 3.71 (like), taste 3.74 (like), crispness 3.78 (like), and overall assessment 3.79 (like).